2018
DOI: 10.1097/md.0000000000012170
|View full text |Cite
|
Sign up to set email alerts
|

Secondary basal cell carcinoma of scalp after radiotherapy

Abstract: Rationale:Radiotherapy (RT) is widely used for both malignant and benign tumors in order to reduce the risk of recurrence, to promote tumor control, and to improve survival. However, there have been studies reported that RT is also a risk factor of secondary cancer. Very few cases of secondary malignancy after RT to high grade brain cancer have been reported due to short survival of this disease, and most RT-induced malignancies presented with sarcomatous histology. Here we present a patient with basal cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A cohort study conducted in 2011 using data from the U.S. Surveillance, Epidemiology, and End Results cancer registries reported that approximately 8% of all second solid tumors in adult cancer survivors may be related to the radiation therapy for the original cancer [11]. Evidence of radiation-induced skin cancers has been reported in uranium miners, radium dial painters, radiologists, and patients with a history of using early World War II-era highvoltage cathode-ray tube oscilloscopes, as well as in patients treated with X-rays for childhood acne, tinea capitis, or thymic enlargement [7,8]. Possible mechanisms of the development of radiation-associated BCC include radiation-related DNA damage, which induces an intricate range of cellular responses involving the cell signaling pathways implicated in the progression of radiation-induced tumors over time, as well as other factors that may make patients more susceptible to radiation-induced BCCs [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cohort study conducted in 2011 using data from the U.S. Surveillance, Epidemiology, and End Results cancer registries reported that approximately 8% of all second solid tumors in adult cancer survivors may be related to the radiation therapy for the original cancer [11]. Evidence of radiation-induced skin cancers has been reported in uranium miners, radium dial painters, radiologists, and patients with a history of using early World War II-era highvoltage cathode-ray tube oscilloscopes, as well as in patients treated with X-rays for childhood acne, tinea capitis, or thymic enlargement [7,8]. Possible mechanisms of the development of radiation-associated BCC include radiation-related DNA damage, which induces an intricate range of cellular responses involving the cell signaling pathways implicated in the progression of radiation-induced tumors over time, as well as other factors that may make patients more susceptible to radiation-induced BCCs [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several reports have characterized radiogenic BCC as generally more aggressive, difficult to excise completely, and more likely to recur than non-radiogenic BCC 9 10 . Therefore, it is important to conduct a close physical examination, especially of areas previously exposed to radiation, in patients with a history of radiation treatment 7 8 9 11 . Here, we report a case of ABCC that showed unique histological and morphological features in a patient with a history of radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed few publications are confirming such existence, but the majority of patients do not survive after radiotherapy to develop secondary cancers such as basal cell carcinoma. 26 However, the role of CHEK2 mutation in itself driving this or increasing radiosensitisation as a result of the underlying mutation cannot be discounted as well. We hypothesise the development of his basal cell carcinoma in this male to be most likely multifactorial.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…In addition, scalp BCCs have also been reported in patients who have received radiotherapy for brain tumors. [1] Although hair would be presumed to offer relative sun protection to the scalp, some reports suggested an increased incidence of scalp BCCs, mainly in younger women. [2]…”
Section: Answermentioning
confidence: 99%